Pertumbuhan dan Produksi Padi Inpari 31 pada Musim yang Berbeda - Hikmah, Zaqiah Mambaul; Pratiwi, Gagad Restu (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Cropping systems is one of the efforts to increase the yield of rice through the manipulation of plant spacing. Legowo rows is one of the methods in manipulating population to increase yield. However, high population with dense plants causes risk to fall when the rainy season. The purpose of this research is to know the effect of cropping system, seedling age, season on the growth and yield of Inpari 31. This research was conducted at Sukamandi for 2 seasons,in 2015 to 2016. Using a split-split plot design with the main plot of the season that is the dry season and the rainy season, planting system is sub plot with 3 levels : tegel, legowo 2:1, and 4:1. The age seedling is sub sub plot. The variable consisted tall of plant, number of tiller, and yield. The results showed that the age, plant spacing, season influenced the results significantly. The yield of age 20 DAS (day after sowing) higher than 30 DAS. During the dry season the yield was higher compared with the rainy season. In the dry season, the yield of legowo 2:1 was higher (7.69 tons/ha GKG) compared to legowo 4:1 and tegel (6.77 tons/ha GKG). However, the application of the planting system does not have a significant effect on increasing yieldsin rainy season.